Nanofiber felt with nonlinear volt-ampere characteristic, epoxy resin composite material and preparation method

By doping metal oxide semiconductors of different Fermi levels in nanofibers and preparing nanofiber felts using electrospinning technology, combining epoxy resin to form composite materials, the electric field distortion of traditional insulating materials under local discharge and charge accumulation is solved. Problem, excellent nonlinear voltammetry characteristics and charge adaptive dissipation performance at low doping rates are achieved.

CN119411314AActive Publication Date: 2025-02-11SHENZHEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411459968.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-11
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Traditional insulating materials are difficult to adapt to electric field distortion caused by local discharge or charge accumulation of electrical and electronic devices, and SiC-filled smart dielectric materials cannot obtain excellent nonlinear voltammetry characteristics when Schottky barrier is low.

Method used

Nanofibers with high Schottky barriers were synthesized by doping metal oxide semiconductors with different Fermi levels, and nanofiber felts with three-dimensional porous network structure were prepared by electrospinning technology, and they were combined with epoxy Resin is composited to form a composite material with nonlinear voltammetry characteristics.

Benefits of technology

It achieves excellent nonlinear voltammetry characteristics under low doping rates, solves the problem of taking into account between nonlinear voltammetry performance and charge adaptive dissipation performance, and improves the insulation level and electric field distribution uniformity of high-voltage electrical equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411314A_ABST
    Figure CN119411314A_ABST
Patent Text Reader

Abstract

The invention relates to a nanofiber felt with nonlinear volt-ampere characteristics, an epoxy resin composite material and a preparation method, and belongs to the technical field of electrical and electronic insulating materials. The nanofiber felt with the nonlinear volt-ampere characteristic is of a three-dimensional porous network structure formed by non-directional stacking of nanofibers, and the nanofibers are formed by assembling silicon carbide, tungsten trioxide and gallium sesquioxide. According to the scheme provided by the invention, the nanofiber with a relatively high Schottky barrier is synthesized by utilizing a method of doping metal oxide semiconductors with different Fermi levels, and the problem that the non-linear volt-ampere characteristic of a composite material without a seepage threshold value is not ideal is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrical and electronic insulating materials, and in particular to a nanofiber felt and epoxy resin composite material with nonlinear volt-ampere characteristics and a preparation method thereof. Background Art

[0002] Polymer dielectrics are resistant to high voltage and easy to process, making them a vital packaging material in high-power devices such as electronic products, 5G-6G high-frequency communication substrates, spacecraft and high-voltage converters. However, with the increase in power density and integration, traditional insulating materials are difficult to adapt to the electric field distortion caused by partial discharge or charge accumulation in electrical and electronic devices.

[0003] Related research has found that smart dielectrics that can adaptively control their electrical parameters have been shown to effectively release unnecessary charges to avoid overvoltage. However, for SiC-filled smart dielectric materials, due to the formation of a relatively low Schottky barrier at the interface between the contacting SiC fillers, excellent nonlinear voltammetric characteristics cannot be obtained even if a large amount of fillers are doped. In addition, although the smart dielectric material filled with ZnO microvaristors is designed to have a high double Schottky barrier inside each particle and has good nonlinear performance, due to its random distribution and high percolation threshold, a large amount of filler filling is still required, the nonlinearity lacks stability, and the high doping rate directly increases the difficulty of composite material processing and reduces its mechanical properties. It can be seen that the excellent nonlinear voltammetric performance and low doping rate of composite materials are often mutually exclusive. How to balance excellent nonlinear performance and charge adaptive dissipation performance is the research focus of polymer dielectrics.

[0004] This section merely provides background information related to the present application and is not necessarily prior art. Summary of the invention

[0005] One of the purposes of the present invention is to avoid the shortcomings of the prior art and provide a nanofiber felt with nonlinear volt-ampere characteristics. Nanofibers with higher Schottky barriers are synthesized by doping metal oxide semiconductors with different Fermi levels, thereby solving the problem of unsatisfactory nonlinear volt-ampere performance of composite materials without percolation threshold.

[0006] The second object of the present invention is to provide a method for preparing a nanofiber felt having nonlinear volt-ampere characteristics.

[0007] A third object of the present invention is to provide a method for preparing an epoxy resin composite material.

[0008] A fourth object of the present invention is to provide an epoxy resin composite material.

[0009] One of the purposes of the present invention is achieved through the following technical solutions:

[0010] Provided is a nanofiber felt with nonlinear volt-ampere characteristics. The nanofiber felt has a three-dimensional porous network structure formed by non-directionally stacking nanofibers. The nanofibers are assembled from silicon carbide, tungsten trioxide, and gallium trioxide.

[0011] The second object of the present invention is achieved by the following technical solutions:

[0012] A method for preparing the nanofiber felt having nonlinear voltammetric characteristics is provided, comprising the following steps:

[0013] (1) polycarbosilane, polyethylene oxide, and gallium acetylacetonate are mixed and dissolved in chloroform, and then nano-tungsten trioxide is added and mixed evenly to obtain a mixed dispersion;

[0014] (2) The mixed dispersion is subjected to electrostatic spinning to obtain a nano-polymer fiber felt, which is then wound and assembled and then cured and pyrolyzed to obtain a nano-fiber felt doped with gallium trioxide and tungsten trioxide.

[0015] In some embodiments, in step (1), the ratio of the added amounts of polycarbosilane, polyethylene oxide, gallium acetylacetonate and nano-tungsten trioxide is 1 g: (0.12-0.36 g): (8-15 mL): (0.03-0.09 g).

[0016] In some embodiments, in step (2), the electrospinning solution insertion rate is set to 200 mm / s, the applied voltage is 60 kV, the collector distance is 24 mm, the curing temperature is 200° C., and the curing time is 5 h.

[0017] In some embodiments, in step (2), the pyrolysis is specifically:

[0018] Under the protection of inert gas, the solidified material is pyrolyzed at a temperature of 1300°C, and the heating rate of the pyrolysis is 1°C / min.

[0019] The third object of the present invention is achieved by the following technical solutions:

[0020] Provided is a method for preparing an epoxy resin composite material, the preparation method comprising:

[0021] The epoxy resin matrix, the curing agent and the accelerator are uniformly mixed to obtain an epoxy resin mixture, and then the nanofiber felt is immersed in the epoxy resin mixture, and the nanofiber felt impregnated with the epoxy resin is taken out, and vacuum drying and curing are performed to obtain an epoxy resin composite material;

[0022] The nanofiber felt is the nanofiber felt with nonlinear volt-ampere characteristics mentioned above or the nanofiber felt with nonlinear volt-ampere characteristics obtained by the above preparation method.

[0023] In some embodiments, the volume fraction of the nanofiber mat is 0.3% to 2% of the epoxy resin composite material.

[0024] In some embodiments, the epoxy resin matrix includes at least one of a bisphenol A epoxy resin, an alicyclic epoxy resin, and a biphenyl epoxy resin;

[0025] The curing agent is methyl hexahydrophthalic anhydride or methyl tetrahydrophthalic anhydride;

[0026] The accelerator includes at least one of DMP30, triethylamine and 2-ethyl 4-methylimidazole;

[0027] The component ratio of the epoxy resin matrix, the curing agent and the accelerator is 100:(70-120):(0.1-1).

[0028] In some embodiments, the vacuum drying process is performed at a temperature of 70° C. and a vacuuming time of 12 h;

[0029] The curing process is specifically as follows:

[0030] The first stage curing treatment, the second stage curing treatment and the third stage curing treatment are performed in sequence. The curing temperature of the first stage curing treatment is 105°C and the curing time is 1 hour; the curing temperature of the second stage curing treatment is 115°C and the curing time is 1 hour; the curing temperature of the third stage curing treatment is 135°C and the curing time is 1 hour.

[0031] The fourth object of the present invention is achieved by the following technical solutions:

[0032] Provided is an epoxy resin composite material, which is prepared by the above preparation method.

[0033] The technical solution provided by this application may have the following beneficial effects:

[0034] (1) The nanofiber felt provided in the present application has nonlinear volt-ampere characteristics, and polarity reversal does not affect the nonlinear volt-ampere characteristics of the nanofibers, and the threshold field strength change does not exceed 2V / mm. The nonlinear coefficient of the nanofiber felt is greater than 10 for tungsten trioxide and gallium trioxide at different doping concentrations, and has a stable double Schottky barrier. The nonlinear volt-ampere characteristics are not affected by the randomness of the nanofiber arrangement.

[0035] (2) The nanofiber felt with nonlinear volt-ampere characteristics provided in the present application solves the problem that nonlinear volt-ampere characteristics and low doping rate are often mutually exclusive. While maintaining excellent nonlinear performance and charge adaptive dissipation performance, it can also significantly reduce the volume fraction of the nanofiber felt in the epoxy resin composite material.

[0036] (3) The method for preparing the nanofiber felt with nonlinear volt-ampere characteristics provided in the present application is to electrospin a mixed solution of polycarbosilane, polyethylene oxide, gallium acetylacetonate, and nano-tungsten trioxide, and obtain a nanofiber felt with a three-dimensional structure by non-directional stacking. The randomness of the arrangement of the nanofibers does not affect its own nonlinear volt-ampere characteristics. It has a stable double Schottky barrier, can improve the insulation level of high-voltage electrical equipment and regulate the spatial electric field distribution of high-voltage electrical equipment, and ensure the safe and stable operation of the electrical equipment.

[0037] (4) The preparation method of the epoxy resin composite material provided in the present application has a simple process and can be used for industrial production.

[0038] (5) The epoxy resin composite material provided in the present application, the nanofiber felt, at a filling amount of 0.3%, achieves excellent nonlinear volt-ampere characteristics of the epoxy resin composite material through its own continuous seepage path and aspect ratio, and the ratio of tungsten to gallium in the nanofiber felt does not affect the nonlinear volt-ampere characteristics of the epoxy resin composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail the exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0040] Figure 1 Transmission electron microscope image, element mapping image, X-ray diffraction image and X-ray photoelectron spectroscopy image of the nanofiber mat prepared in Example 1;

[0041] Figure 2 The atomic force microscope image of the nanofiber mat prepared in Example 1 and the nonlinear voltammetric characteristic test graphs of the nanofiber mat prepared in Examples 1 to 5;

[0042] Figure 3 This is a SEM image of the epoxy resin composite material prepared in Example 6;

[0043] Figure 4 The nonlinear volt-ampere characteristic curves of the epoxy resin composite materials prepared in Examples 6 to 13. DETAILED DESCRIPTION

[0044] The preferred embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the preferred embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0045] Improving the insulation level of high-voltage electrical equipment and regulating the spatial electric field distribution are one of the core issues in the research and development and manufacturing of advanced electrical equipment. Developing intelligent insulating materials that can adapt to complex service environments, achieving adaptive matching of their electrical properties and external electric fields, and effectively regulating the uniformity of the electric field are of great significance to the development of advanced electrical materials and the safe and stable operation of electrical equipment.

[0046] In view of the above problems, the present invention provides a nanofiber felt and epoxy resin composite material with nonlinear volt-ampere characteristics and a preparation method thereof.

[0047] The present invention is further described in detail below with reference to the examples. All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.

[0048] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials of conventional purity used in the field of resin materials.

[0049] In a typical embodiment of the present invention, a nanofiber felt with nonlinear volt-ampere characteristics is provided. Nanofibers with a higher Schottky barrier are synthesized by doping metal oxide semiconductors with different Fermi levels, thereby solving the problem of unsatisfactory nonlinear coefficients of composite materials without percolation threshold and effectively improving the nonlinear volt-ampere performance of the nanofibers.

[0050] In one embodiment of the present invention, a nanofiber felt having nonlinear volt-ampere characteristics is provided. The nanofiber felt has a three-dimensional porous network structure formed by non-directionally stacking nanofibers, and the nanofibers are assembled from silicon carbide, tungsten trioxide, and gallium trioxide.

[0051] When studying high-voltage electrical equipment, the inventor discovered that nanofibers made of silicon carbide, tungsten trioxide and gallium trioxide by electrostatic spinning were wound and assembled into non-oriented nanofiber felts, which were then combined with epoxy resin. Experimental results show that the epoxy resin composite material has excellent nonlinear volt-ampere characteristics at a filling amount of 0.3 vol% due to the continuous percolation path of the nanofiber felt and the extremely high aspect ratio of the nanofibers, and the threshold field strength gradually decreases as the filling volume fraction increases. In addition, at the same volume fraction of the nanofiber felt, the threshold field strength is close to that of different tungsten gallium content ratios in the epoxy resin composite material. It can be seen that when the volume fraction of the nanofiber felt in the epoxy resin composite material is the same, the threshold field strength is positively correlated with the total mass fraction of the doped metal oxide semiconductor, and the tungsten gallium content ratio has little effect on this.

[0052] In another embodiment of the present invention, a method for preparing a nanofiber felt having nonlinear voltammetric characteristics is provided, the method comprising:

[0053] (1) polycarbosilane, polyethylene oxide, and gallium acetylacetonate are mixed and dissolved in chloroform, and then nano-tungsten trioxide is added and mixed evenly to obtain a mixed dispersion;

[0054] (2) The mixed dispersion is subjected to electrostatic spinning to obtain a nano-polymer fiber felt, which is then wound and assembled and then cured and pyrolyzed to obtain a nano-fiber felt doped with gallium trioxide and tungsten trioxide.

[0055] Furthermore, in step (1) of the above-mentioned method for preparing a nanofiber felt having nonlinear voltammetric characteristics, the ratio of the added amounts of polycarbosilane, polyethylene oxide, gallium acetylacetonate and nano tungsten trioxide is 1g: (0.12-0.36g): (8-15mL): (0.03-0.09g).

[0056] The electrospinning of the present invention is a method well known to those skilled in the art, and there is no special restriction. The solution insertion rate of the electrospinning is set to 120-280 mm / s, preferably 150-250 mm / s, more preferably 180-220 mm / s, the applied voltage of the electrospinning is 55-65 kV, preferably 58-63 kV, more preferably 60 kV, the collector distance is 20-30 mm, preferably 22-28 mm, more preferably 24-26 mm; the curing temperature of the electrospinning is 150-250 ° C, preferably 180-220 ° C, more preferably 200 ° C, and the curing time of the electrospinning is 3-7 h, preferably 4-6 h, more preferably 5 h.

[0057] Furthermore, in step (2) of the above-mentioned method for preparing the nanofiber felt having nonlinear voltammetric characteristics, the pyrolysis is specifically:

[0058] Under the protection of inert gas, the solidified material is pyrolyzed at a temperature of 1300°C, and the heating rate of the pyrolysis is 1°C / min.

[0059] In another embodiment of the present invention, a method for preparing an epoxy resin composite material is provided, the preparation method comprising:

[0060] The epoxy resin matrix, the curing agent and the accelerator are uniformly mixed to obtain an epoxy resin mixture, and then the nanofiber felt is immersed in the epoxy resin mixture, and the nanofiber felt impregnated with the epoxy resin is taken out, and vacuum drying and curing are performed to obtain an epoxy resin composite material;

[0061] The nanofiber felt is the nanofiber felt with nonlinear volt-ampere characteristics mentioned above or the nanofiber felt with nonlinear volt-ampere characteristics obtained by the above preparation method.

[0062] The present invention has no particular limitation on the epoxy resin, curing agent and accelerator. The epoxy resin, curing agent and accelerator well known to those skilled in the art can be used, and they can be prepared according to conventional methods or purchased commercially.

[0063] The epoxy resin of the present invention includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, brominated epoxy resin, alicyclic epoxy resin and biphenyl epoxy resin, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of bisphenol A epoxy resin and bisphenol F epoxy resin, a combination of bisphenol F epoxy resin and novolac epoxy resin, a combination of novolac epoxy resin and brominated epoxy resin, a combination of brominated epoxy resin and bisphenol A epoxy resin, or a combination of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin, etc.

[0064] The curing agent of the present invention preferably includes one or more of polyamide 300, polyamide 2004, 4-diaminodiphenylmethane, methyl hexahydrophthalic anhydride or methyl tetrahydrophthalic anhydride, more preferably polyamide 300, methyl hexahydrophthalic anhydride or methyl tetrahydrophthalic anhydride, and more specifically preferably methyl hexahydrophthalic anhydride. The present invention has no particular restriction on the amount of the curing agent added. In order to improve the dispersion and composite material performance, the mass ratio of the curing agent to the epoxy resin is preferably 100: (70-120), more preferably 100: (80-100), more preferably 100: (90-95), and most preferably 100: (92-95).

[0065] The accelerator of the present invention preferably includes one or more of DMP30, triethylamine and 2-ethyl 4-methylimidazole, more preferably DMP30 and triethylamine, and more specifically triethylamine. The mass ratio of the accelerator to the epoxy resin is preferably 100:(0.1-1), more preferably 100:(0.3-0.6).

[0066] In the present invention, the volume fraction of the nanofiber felt having nonlinear volt-ampere characteristics is 0.2% to 5% of the epoxy resin composite material, more preferably the volume fraction of the nanofiber felt is 0.25% to 3% of the epoxy resin composite material, more specifically, the volume fraction of the nanofiber felt is 0.3% to 2% of the epoxy resin composite material.

[0067] Specifically, the product of the reaction of polycarbosilane, polyethylene oxide, and gallium acetylacetonate nano-tungsten trioxide is subjected to electrospinning treatment, and the obtained nano-polymer fiber felt is wound and assembled. In the present invention, the volume fraction of the nano-fiber felt in the epoxy resin is determined by adjusting the number of winding layers of the nano-fiber felt. The more the number of winding layers is, the larger the winding volume is, and correspondingly, the larger the volume fraction of the nano-fiber felt is.

[0068] The mixing described in the present invention is preferably heating and stirring mixing. The present invention has no particular limitation on the conditions for the heating and stirring mixing, and the stirring and mixing conditions familiar to those skilled in the art can be used. Those skilled in the art can select and adjust according to actual production conditions, product requirements and quality requirements. The heating temperature described in the present invention is preferably 40-65°C, more preferably 50-60°C; the stirring time described in the present invention is preferably 15-30 minutes, more preferably 17-27 minutes, and most preferably 20-25 minutes; the stirring speed is preferably 1000-2000r / min, more preferably 1200-1800r / min, and most preferably 1400-1600r / min.

[0069] The immersion mentioned in the present invention refers to completely immersing the nanofiber felt in the epoxy resin mixture. In order to improve the dispersion and composite material performance, after the nanofiber felt is completely immersed in the epoxy resin mixture, the container containing the epoxy resin mixture can be placed in a vacuum chamber for vacuum treatment to remove bubbles in the epoxy resin mixture. The pressure of the vacuum treatment is 0.01 to 0.07 MPa, more preferably 0.02 to 0.06 MPa, and most preferably 0.03 to 0.05 MPa.

[0070] The method of taking out the nanofiber felt impregnated with epoxy resin described in the present invention specifically involves taking out the nanofiber felt after it has been immersed for a period of time. Those skilled in the art can select the immersion time of the nanofiber felt according to the types of epoxy resin, curing agent and accelerator, as well as the curing agent of the curing agent. The immersion time described in the present invention is preferably 15 to 30 minutes, more preferably 17 to 27 minutes, and most preferably 20 to 25 minutes.

[0071] Furthermore, the temperature of the vacuum drying treatment in the preparation method of the epoxy resin composite material is 70° C., and the vacuuming time is 12 hours;

[0072] The curing process is specifically as follows:

[0073] The first stage curing treatment, the second stage curing treatment and the third stage curing treatment are performed in sequence. The curing temperature of the first stage curing treatment is 105°C and the curing time is 1 hour; the curing temperature of the second stage curing treatment is 115°C and the curing time is 1 hour; the curing temperature of the third stage curing treatment is 135°C and the curing time is 1 hour.

[0074] To further illustrate the present invention, the nanofiber felt, epoxy resin composite material and preparation method with nonlinear volt-ampere characteristics provided by the present invention are described in detail below in combination with the examples. However, it should be understood that these examples are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.

[0075] In addition, the present invention prepares an epoxy resin composite material through the above steps, which can be specifically named EP / SiC-Ga x W y Composite material, where EP represents epoxy resin, SiC represents silicon carbide, Ga represents gallium, x represents the total mass fraction of gallium in the nanofiber felt, W represents tungsten, and y represents the total mass fraction of tungsten in the nanofiber felt. When x and y are determined, the mass fraction of SiC is determined. During the test, the above EP / SiC-Ga was obtained through transmission electron microscopy, element mapping, X-ray diffraction and X-ray photoelectron spectroscopy. x W y The values ​​of X and Y in the above EP / SiC-Ga x W y This is for reference only and does not mean that the epoxy resin composite material with the above component ratio can be obtained by preparing according to the preparation method of the present invention.

[0076] Example 1: Preparation of SIC-Ga 10 W 10Nanofiber Felt:

[0077] 1. Use 1 g of polycarbosilane, 0.24 g of polyethylene oxide and 10 mL of gallium acetylacetonate as precursors, stir them evenly in chloroform at room temperature with a magnetic stirrer to obtain a dispersion;

[0078] 2. Add 0.03g of nano tungsten trioxide to the dispersion and transfer it to a cutting-edge ultrasonic disperser for ultrasonic dispersion to obtain a mixed dispersion;

[0079] 3. The mixed dispersion was transferred to an electrospinning machine for high-voltage electrospinning. The electrospinning solution insertion rate was set to 200 mm / s, the applied voltage was 60 kV, the collector distance was 24 mm, the curing temperature was 200 ° C, and the curing time was 5 h to obtain a polymer nanofiber felt, which was then wound and assembled and then cured at high temperature in an air oven;

[0080] 4. The cured nanofiber felt was transferred to a high-temperature tube furnace, and the cured material was pyrolyzed at a temperature of 1300°C under the protection of an argon atmosphere, and the pyrolysis heating rate was 1°C / min to obtain a SiC-based nanofiber felt doped with metal oxide semiconductors Ga2O3 and WO3;

[0081] Among them, SIC-Ga 10 W 10 The mass fraction of silicon carbide (SIC) is 80%, the mass fraction of gallium (Ga) is 10%, and the mass fraction of tungsten (W) is 10%.

[0082] Example 2: Preparation of SIC-Ga 10 W 15 Nanofiber Felt:

[0083] Preparation of SIC-Ga 10 W 10 The difference of the nanofiber felt is that the added amount of nano tungsten trioxide is 0.045g.

[0084] Example 3: Preparation of SIC-Ga 10 W 20 Nanofiber Felt:

[0085] Preparation of SIC-Ga 10 W 10 The difference of the nanofiber felt is that the added amount of nano tungsten trioxide is 0.06g.

[0086] Example 4: Preparation of SIC-Ga 15 W 10 Nanofiber Felt:

[0087] Preparation of SIC-Ga 10 W10 The nanofiber mat differed in that the amount of gallium acetylacetonate added was 15 mL.

[0088] Example 5: Preparation of SIC-Ga 15 W 15 Nanofiber Felt:

[0089] Preparation of SIC-Ga 10 W 10 The difference between the nanofiber felt is that the amount of gallium acetylacetonate added is 15 mL and the amount of nano tungsten trioxide added is 0.045 g.

[0090] This application also applies to the above-mentioned SIC-Ga 10 W 10 The nanofiber felt was subjected to TEM test, element distribution test, XRD test and W 4f spectrum test, see Figure 1 .

[0091] Depend on Figure 1 It can be seen that Figure 1 aNanofibers were observed, with a high aspect ratio and uniform diameter of about 100 nm. From the element mapping, it can be seen that the nanofibers contain a large amount of Si, C, O and Ga elements, and the W element can also be clearly seen ( Figure 1 b).

[0092] In order to further characterize the crystal and molecular structural characteristics of nanofibers, the crystal structure of nanofiber mats was observed by X-ray diffractometer, such as Figure 1 c. The strong diffraction peaks at 36.3° and 73.5° correspond to the (111) and (311) crystal planes of SiC, respectively, while the diffraction peaks at 32°, 48.9°, 64.6° and 77.5° correspond to the (104), (024), (214) and (217) crystal planes of Ga2O3, respectively (reference XRD standard card: 01-074-1610). The diffraction peak of WO3 is weaker, with only a slight diffraction peak at 41°, corresponding to the (222) crystal plane (reference XRD standard card: 01-024-0747), which is due to the small particle size (20nm) and low content of nano-WO3.

[0093] XPS was used to further characterize the elemental composition of the nanofiber mat and the valence state of the W element, such as Figure 1 d and Figure 1 e. In the full spectrum, we can observe the peaks of each orbit of the five elements Si, C, O, Ga and W. Combined with the XRD test results, it is shown that there are three compounds of SiC, Ga2O3 and WO3. However, the characteristic peak belonging to the W 4f orbit is masked by the strong characteristic peaks of other elements. Therefore, the characteristic peak of the 4f orbit is locally amplified, as shown in Figure 1As shown in e.

[0094] W4f splits into doublets with binding energy peaks at 34.8 eV and 36.8 eV, corresponding to W 4f 7 / 2 and W4f 5 / 2 Two atomic states, which belong to W 6+ The oxidation state of WO3 is also revealed.

[0095] The present application conducted an AFM test on the nanofiber felt prepared in Example 1, and conducted radial voltammetric characteristic tests on the nanofiber felt prepared in each of the above examples. Figure 2 and Table 1.

[0096] When performing AFM testing on nanofiber mats, the nanofiber mats are evenly dispersed on a conductive substrate and placed under an atomic force microscope to find single nanofibers that are not in contact with the surroundings. Then, the conductive atomic force microscope mode is used to move the conductive probe to directly contact the nanofibers. The scanning image and test principle diagram are shown in the figure. Figure 2 The probe is connected to a DC source and an ammeter, with a tip radius of 25 nm and a length of about 10-15 μm. Finally, the nonlinear voltammetric characteristics of a single nanofiber are tested by applying a scanning voltage with a scanning frequency of 0.5 Hz, and the uniformity and stability of the nonlinear voltammetric characteristics of the nanofiber under positive bias and negative bias are verified. The results are shown in Figure 2 b and Table 1. Figure 2 b It can be seen that the volt-ampere characteristics of the nanofiber felts in all the embodiments show similar variation patterns, and as the doping concentration of Ga2O3 or WO3 increases, the varistor voltage will decrease significantly. It is worth noting that the nonlinear coefficients of the nanofibers under different GaW doping concentrations are all greater than 10. From the comparison of the nonlinear characteristic parameters after applying positive and negative bias voltages in Table 1, it can be seen that polarity reversal has almost no effect on the nonlinear volt-ampere characteristics of the nanofiber felt, the threshold field strength changes by no more than 2V / mm, and the nonlinear coefficient is relatively stable. This shows that the synthesized nanofiber felt is uniformly doped with Ga2O3 and WO3, has a stable double Schottky barrier, and its nonlinear volt-ampere characteristics are not affected by the randomness of the fiber arrangement.

[0097] Table 1 Nonlinear coefficient and threshold field strength of nanofiber mat

[0098]

[0099]

[0100] Embodiment 6:

[0101] (1) 100 parts by mass of bisphenol A epoxy resin, 70 parts by mass of methyltetrahydrophthalic anhydride and 0.5 parts by mass of triethylamine were stirred at 60° C. for 30 minutes;

[0102] (2) The SiC-Ga 15 W 15 The nanofiber felt was immersed in the epoxy resin mixture until it was completely infiltrated. The mixed system was then transferred to a high-temperature vacuum drying oven for continuous vacuuming at a vacuum drying temperature of 70°C for 12 hours until no bubbles emerged.

[0103] (3) The nanofiber felt completely impregnated with epoxy resin was taken out and transferred to a stainless steel mold, and then cured at 105°C for 1 hour, then at 115°C for 1 hour, and finally at 135°C for 1 hour to prepare a 0.3 vol% SiC-Ga 15 W 15 Epoxy composite material.

[0104] Example 7

[0105] The difference from Example 6 is that the prepared 15 W 15 Epoxy composite material.

[0106] Example 8

[0107] The difference from Example 6 is that the prepared 15 W 15 Epoxy composite material.

[0108] Example 9

[0109] The difference from Example 6 is that the prepared 15 W 15 Epoxy composite material.

[0110] Example 10

[0111] The difference from Example 6 is that the SiC-Ga prepared in Example 3 10 W 20 The nanofiber felt was immersed in an epoxy resin mixture to prepare a 0.3 vol% SiC-Ga 15 W 15 Epoxy composite material.

[0112] Embodiment 11

[0113] The difference from Example 10 is that the prepared 15 W 15 Epoxy composite material.

[0114] Example 12

[0115] The difference from Example 10 is that the prepared 15 W 15 Epoxy composite material.

[0116] Embodiment 13

[0117] The difference from Example 10 is that the prepared 15 W 15 Epoxy composite material.

[0118] The present application conducted SEM testing on the epoxy resin composite material prepared in Example 6, and conducted nonlinear coefficient and threshold field strength testing on the epoxy resin composite materials prepared in Examples 6 to 13. Figure 3 , nonlinear coefficient and threshold field strength see Figure 4 and Table 2.

[0119] Table 2 Nonlinear coefficients and threshold field strengths of Examples 6 to 13

[0120]

[0121] When the epoxy resin composite material prepared in Example 6 was subjected to SEM testing, a field emission scanning electron microscope was used to characterize the epoxy resin composite material containing the nanofiber felt. In order to clearly observe the nanofibers on the surface of the composite material, a laser cutting machine was used to laser ablate the epoxy resin on the surface of the material, thereby exposing the arrangement of the nanofibers on the surface of the composite material, such as Figure 3 As shown. The coiled nanofibers can be clearly observed on the surface of the material. The fibers are filled with a well-cured epoxy resin matrix, and no obvious interface defects are found. Figure 3 It can be seen that the nanofibers composed of tungsten oxide, gallium trioxide and silicon carbide form a closely contacted linear conduction path. Therefore, when there is a local electric field unevenness and local discharge occurs, it can serve as a complete charge release path and quickly conduct and release along the arrangement direction.

[0122] In order to explore the effect of epoxy resin composites filled with nanofiber mats with different volume fractions on the nonlinear voltammetric characteristics, the EP / SiC-Ga nanofiber mats with different volume fractions were compared. 15 W 15 and EP / SiC-Ga 10 W 20 The nonlinear voltammetric characteristics of composite materials, such as Figure 4As shown in Table 2. The results show that the epoxy resin composite material has excellent nonlinear voltammetric characteristics at extremely low filling content (0.3 vol%), which is due to the continuous percolation path of the nanofiber mat and the extremely high aspect ratio of the nanofiber. As the filling volume fraction increases, the threshold field strength gradually decreases. However, at the same volume fraction, EP / SiC-Ga 15 W 15 and EP / SiC-Ga 10 W 20 The threshold field strength of the composite materials is close, indicating that when the volume fraction of the nanofiber mat is the same, the threshold field strength is related to the total mass fraction of the doped metal oxide semiconductor. In addition, as shown in Table 2, the nonlinear coefficient of the composite materials at all filling volume fractions is about 10, indicating that the epoxy resin composite material has extremely high nonlinear stability and can meet the requirements of uniform electric field of power transmission and transformation equipment.

[0123] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A nanofiber felt having nonlinear voltammetric characteristics, characterized in that: The nanofiber felt is a three-dimensional porous network structure formed by non-directionally stacking nanofibers, and the nanofibers are assembled from silicon carbide, tungsten trioxide, and gallium trioxide.

2. A method for preparing a nanofiber mat having nonlinear volt-ampere characteristics as claimed in claim 1, characterized in that: The preparation method comprises: (1) polycarbosilane, polyethylene oxide, and gallium acetylacetonate are mixed and dissolved in chloroform, and then nano-tungsten trioxide is added and mixed evenly to obtain a mixed dispersion; (2) The mixed dispersion is subjected to electrostatic spinning to obtain a nano-polymer fiber felt, which is then wound and assembled and then cured and pyrolyzed to obtain a nano-fiber felt doped with gallium trioxide and tungsten trioxide.

3. The method for preparing the nanofiber mat having nonlinear volt-ampere characteristics according to claim 2, characterized in that: In the step (1), the ratio of the added amounts of polycarbosilane, polyethylene oxide, gallium acetylacetonate and nano-tungsten trioxide is 1 g: (0.12-0.36 g): (8-15 mL): (0.03-0.09 g).

4. The method for preparing the nanofiber mat having nonlinear volt-ampere characteristics according to claim 2, characterized in that: In the step (2), the electrospinning solution insertion rate is set to 200 mm / s, the applied voltage is 60 kV, the collector distance is 24 mm, the curing temperature is 200° C., and the curing time is 5 h.

5. The method for preparing the nanofiber mat having nonlinear volt-ampere characteristics according to claim 4, characterized in that: In the step (2), the pyrolysis is specifically: Under the protection of inert gas, the solidified material is pyrolyzed at a temperature of 1300°C, and the pyrolysis heating rate is 1°C / min.

6. A method for preparing an epoxy resin composite material, characterized in that: The preparation method comprises: The epoxy resin matrix, the curing agent and the accelerator are uniformly mixed to obtain an epoxy resin mixture, and then the nanofiber felt is immersed in the epoxy resin mixture, and the nanofiber felt impregnated with the epoxy resin is taken out, and vacuum drying and curing are performed to obtain an epoxy resin composite material; The nanofiber felt is the nanofiber felt with nonlinear volt-ampere characteristics as claimed in claim 1 or the nanofiber felt with nonlinear volt-ampere characteristics obtained by the preparation method as claimed in any one of claims 2 to 5.

7. The method for preparing the epoxy resin composite material according to claim 6, characterized in that: The volume fraction of the nanofiber felt is 0.3% to 2% of the epoxy resin composite material.

8. The method for preparing the epoxy resin composite material according to claim 7, characterized in that: The epoxy resin matrix includes at least one of bisphenol A epoxy resin, alicyclic epoxy resin and biphenyl epoxy resin; The curing agent is methyl hexahydrophthalic anhydride or methyl tetrahydrophthalic anhydride; The accelerator includes at least one of DMP30, triethylamine and 2-ethyl 4-methylimidazole; The component ratio of the epoxy resin matrix, the curing agent and the accelerator is 100:(70-120):(0.1-1).

9. The method for preparing the epoxy resin composite material according to claim 6, characterized in that: The vacuum drying temperature is 70°C and the vacuuming time is 12h; The curing process is specifically as follows: The first stage curing treatment, the second stage curing treatment and the third stage curing treatment are performed in sequence. The curing temperature of the first stage curing treatment is 105°C and the curing time is 1 hour; the curing temperature of the second stage curing treatment is 115°C and the curing time is 1 hour; the curing temperature of the third stage curing treatment is 135°C and the curing time is 1 hour. 10 . An epoxy resin composite material, prepared by the method for preparing an epoxy resin composite material according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Manufacturing method of flexible zirconia nanofiber phosphorylated peptide enrichment material

    CN109112721A

  • Conductive film and electronic device having conductive film

    WO2014188822A1

  • Quantum dot betavoltaic battery

    WO2019113842A1

  • Polymer-based modifying interlayer for lithium anode and solid electrolyte interface and method of preparing the same

    WO2024097083A1

  • KR20240036042A